Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 8 - Sections 8.1-8.3 - Integrated Review - Summary on Solving Quadratic Equations: 12

Answer

$x=\dfrac{-1\pm i\sqrt{11}}{2}$

Work Step by Step

Using the properties of equality, the given quadratic equation, $ x^2+x=-3 ,$ is equivalent to \begin{array}{l}\require{cancel} x^2+x+3=0 .\end{array} Using $x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}$ or the Quadratic Formula, the solutions of the quadratic equation above are \begin{array}{l}\require{cancel} x=\dfrac{-1\pm\sqrt{1^2-4(1)(3)}}{2(1)} \\\\ x=\dfrac{-1\pm\sqrt{1-12}}{2} \\\\ x=\dfrac{-1\pm\sqrt{-11}}{2} \\\\ x=\dfrac{-1\pm\sqrt{-1}\cdot\sqrt{11}}{2} \\\\ x=\dfrac{-1\pm i\sqrt{11}}{2} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.